A Novel, New Robotic Platform for Natural Orifice Distal Pancreatectomy. (June 2015) - Thakkar, Shyam; Awad, Michael; Gurram, Krishna C.; Tully, Steven; Wright, Cornell; Sanan, Siddharth; Choset, Howie
Laparoendoscopic technology has revolutionized the practice of surgery; however, surgeons have not widely accepted laparoscopic techniques for pancreatic surgeries due to the complexity of the operation. Natural orifice transluminal endoscopic surgery (NOTES) offers a great new potential for pancreatic procedures, with early data showing benefits of reduced visible scarring and the potential for decreased wound infections, hernias, pain, and postoperative complications. However, there are significant limitations to the currently used flexible endoscopy tools, including a diminished visual field, spatial orientation and tissue manipulation issues, and 2-dimensional visual feedback. We have adopted a novel snake-like robot, the minimally invasive cardiac surgery (MICS) robot, which addresses these issues. In the current pilot study, the MICS robot was evaluated for transrectal distal pancreas exploration and resection in 2 nonsurvival porcine models. Abdominal navigation and accessing the pancreas was investigated in the first pig, and based on its success, pancreas resection was studied in pig 2. The MICS robot was successful in accessing and visualizing the right upper, left upper, and left lower quadrants of the abdomen in pig 1 and was able to perform a successful complex NOTES procedure with distal pancreas resection in pig 2, with only minimal laparoscopic retraction assistance. In conclusion, preliminary results showing the MICS robot in natural orifice distal pancreatectomy are positive. Enhancements to optics and instrumentation will help further increase the usability in pancreatic interventions. Future indications may include transgastric NOTES approaches, endoluminal procedures, and single-port applications.